Propagation of the sound wave by an unclosed spherical shell and a penetrable ellipsoid - Gennady Shushkevich (Advances in Mechanical and Materials Engineering, 2016)
In this paper the result of solution of axisymmetric problem of propagation of sound wave by an unclosed spherical shell and a penetrable ellipsoid of rotation is presented. A spherical radiator is located in a thin unclosed spherical shell as a source of acoustic field. The equation of the spheroidal boundary is given in spherical coordinates. A scattered pressure field is expressed in terms of spherical wave functions. Using corresponding additional theorems the solution of boundary value problem is reduced to solving of dual equations in Legendre's polynomials, which are converted to infinite system of linear algebraic equations of the second kind. The formula for calculation of the far field and numerical results for different values of parameters are obtained.